Review of the existing maximum residue levels for dithianon according to Article 12 of Regulation (EC) No 396/2005. (9th January 2023) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Binaglia, Marco; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Castoldi, Anna Federica; Chiusolo, Arianna; Crivellente, Federica; Del Aguila, Monica; Ferreira, Lucien; et al.
Abstract: According to Article 12 of Regulation (EC) No 396/2005, EFSA has reviewed the maximum residue levels (MRLs) currently established at European level for the pesticide dithianon. To assess the occurrence of dithianon residues in plants, processed commodities, rotational crops and livestock, EFSA considered the conclusions derived in the framework of Commission Regulation (EC) No 33/2008, the MRLs established by the Codex Alimentarius Commission as well as the European authorisations reported by Member States and the UK, including the supporting residues data. Given that a data gap as regards the magnitude of residues of the metabolites 1, 4‐naphthoquinone and phthalic acid was identified in the peer review for dithianon in light of confirmatory data, the toxicological profile of these metabolites was also assessed in the framework of the Article 12 MRL review. Based on the assessment of the available data, MRL proposals were derived and a consumer risk assessment was carried out. Although no apparent risk to consumers was identified, some information required by the regulatory framework was missing. In particular, it is highlighted that the toxicological reference values derived for the metabolite 1, 4‐naphthoquinone are provisional only, pending a conclusion on the mutagenicity potential. Hence, the consumer risk assessment is considered indicative only and some MRL proposals derived by EFSA still require further consideration by risk managers.